Augmented Reality as Catalyst for Digital Literacy Enhancement: Investigating University Students’ Readiness in the Era of Disruptive Educational Technologies - Prabowo, Suryo; Andayani, Andayani (International Journal of Education and Learning Studies, 2025)
This study investigates the extent to which university students’ readiness for Augmented Reality (AR) can enhance digital literacy in technology-integrated learning environments. Using a quantitative survey design, data were collected from 356 Educational Technology students at an open university. The study measured five dimensions of digital literacy and four indicators of AR readiness. Results revealed moderate to high digital literacy levels, with significant positive correlations between all AR readiness indicators and digital literacy domains. Multiple regression analysis showed that perceived usefulness and confidence in using AR were the strongest predictors of digital competence. These findings underscore AR’s role as a transformative medium for fostering 21st-century skills, especially when student readiness is addressed through targeted pedagogical interventions. The study offers empirical insights to inform curriculum design, emphasizing the integration of immersive technologies not only to support content delivery but to actively cultivate digital fluency.